Elevated temperature alters bacterial community composition and metabolism in seawaters of coral reef ecosystem: An evidence of laboratory experiment with Acropora digitifera bleaching. (June 2022) - Sun, Hao; Zheng, Huina; Jiang, Yiwei; Liang, Jinchang; Liao, Baolin; Wang, Ruixuan; Li, Aihua; Xiao, Baohua
Graphical abstract: Highlights: Microbial community in seawater surrounding corals changed under thermal stress. Stress tolerance, biofilm forming and mobile elements increased under thermal stress. DMSP production and catabolism in seawater enhanced as temperature increasing. Abstract: The global phenomenon of coral bleaching under thermal stress has been recognized as the primary driver underlying coral reef degradation. The coral bacterial community plays an important role in the stability of coral reef ecosystem. Dimethylsulfoniopropionate (DMSP) and its associated metabolites are essential for the establishment of coral bacterial communities and provide key benefits for overall coral health and bleaching recovery. Substantial research to date has focused on the bacterial community composition, metabolism and functional properties within the coral holobiont, but less attention has been paid to the role of bacteria in seawater surrounding corals under thermal stress. Here, we investigated bacterial community composition, biological functions and DMSP metabolism changes of the seawater surrounding corals under thermal stress. We found that microbial community in seawater surrounding corals changed under thermal stress, and corals bleached eventually. The abundance of Rhodobacterales, Flavobacteriales and Rhizobiales increased while Chitinophagales and SAR11 decreased as temperature elevated. Correspondingly, stress tolerant, biofilm forming and mobile elements increased, resulting in large part from changes in Rhodobacterales and Phaeodactylibacter abundance. DMSP producing and catabolic levels in seawater surrounding corals were enhanced under thermal stress with higher dsyB (1.46-fold), dddP (2.43-fold) and dmdA (1.47-fold) detected. This study reveals the biological functions and metabolisms of bacteria in the water surrounding corals, providing valuable insight on how these communities and functions change in coral reef ecosystem under thermal stress.